2017
DOI: 10.3897/phytokeys.88.14674
|View full text |Cite
|
Sign up to set email alerts
|

The Mosses of Crocker Range Park, Malaysian Borneo

Abstract: This paper reports the mosses from Crocker Range Park (CRP) in Sabah, Malaysian Borneo. In total, 293 species, three subspecies and eight varieties belonging to 118 genera and 36 families are reported. This represents about 40% and 47% of the species and infra-specific taxa reported from Borneo and Sabah, respectively. Out of these, six species are new records for Borneo, namely Barbella horridula, Chaetomitrium lancifolium, Distichophyllum leiopogon, Rhaphidostichum luzonense, Rosulabryum capillare and Taxiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…The most recent record of moss species for the Borneo region was reported by (Suleiman, Masundang and Akiyama, 2017) 6 species, namely Barbella horridula, Chaetomitrium lancifolium, Distichophyllum leiopogon, Rhaphidostichum luzonense, Rosulabryum capillare and Taxiphyllum taxirameum. Furthermore, in 2018 there were 2 types of Fissidentaceae, namely F. bogoriensis and F. braunii which are the new records for Borneo (Sarah Agustiorini, 2018).…”
Section: New Record and New Speciesmentioning
confidence: 99%
“…The most recent record of moss species for the Borneo region was reported by (Suleiman, Masundang and Akiyama, 2017) 6 species, namely Barbella horridula, Chaetomitrium lancifolium, Distichophyllum leiopogon, Rhaphidostichum luzonense, Rosulabryum capillare and Taxiphyllum taxirameum. Furthermore, in 2018 there were 2 types of Fissidentaceae, namely F. bogoriensis and F. braunii which are the new records for Borneo (Sarah Agustiorini, 2018).…”
Section: New Record and New Speciesmentioning
confidence: 99%
“…Reports of the species by Brotherus (1928), Herzog (1928), Dixon (1935) and Touw (1978) indicated that E. ptychofolium was widely distributed within, and endemic to, Borneo (Nishimura 1984). Further Bornean records were found in Sabah (Suleiman and Edwards 2002;Suleiman et al 2011Suleiman et al , 2017. However, Tan et al (2000) and Tan and Shevock (2014) reported its presence outside Borneo, in Mindanao Island in the Philippines.…”
Section: Contributor H Bednarek-ochyramentioning
confidence: 94%
“…Nomenclature of mosses follows Goffinet et al (2009) and Goffinet and Buck (2010) with some modification, while genera and species were arranged in alphabetical order. The status of new records for Borneo was evaluated using relevant literature (Suleiman and Edward 2002;Suleiman et al 2003Suleiman et al , 2006Suleiman et al , 2009Suleiman et al , 2011aSuleiman et al , 2011bSuleiman et al , 2017aSuleiman et al , 2017bAkiyama 2004, 2007;Andi and Suleiman 2005;Higuchi et al 2008 Photographs of diagnostic characters of the new records were taken using Olympus Digital Camera DP72 at the Phytochemistry Laboratory of Forest Research Centre (FRC), Sabah Forestry Department, Malaysia.…”
Section: Methodsmentioning
confidence: 99%